Sexual practices among unmarried adolescents in Tanzania - Masatu Melkiory C; Kazaura Method R (BMC, 2009)
Abstract Background Sexual activities are increasingly changing from the cultural point of view what they used to be. Knowledge of these practices among adolescents may be a basis to create awareness among adolescents on practices that involve risks. This study aims to assess sexual practices among unmarried adolescents in Tanzania. Methods A cross-sectional survey was conducted among in-school and out-of-school but unmarried adolescents aged 10 to 19 in five locations in Tanzania. A questionnaire was used to collect information and to characterize sexual practices among these adolescents. Results About 32% of adolescents reported being sexually active; a higher proportion being males than females. The only inquired and reported sexual practices include vaginal sex, masturbation, oral and anal sex. About 15% of sexually active adolescents reported having multiple sexual partners. Significantly more males reported having multiple partners than females. Nearly 42% of sexually active adolescents reported having used a condom during most recent sexual act. Females reported older partners at first sexual act. Conclusion Adolescents experience several sexual practices that include penetrative and non-penetrative. More males reported being sexually active than females. Despite adolescents reporting having multiple sexual partners, reported condom use during the most recent sexual act was low. We advocate for a more enhanced approach of reproductive health education that includes safer sex to adolescents without forgetting those in-schools.